2006
DOI: 10.1542/peds.2005-1817
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Promotion and the Initiation of Tobacco Use: Assessing the Evidence for Causality

Abstract: Promotions foster positive attitudes, beliefs, and expectations regarding tobacco use. This fosters intentions to use and increases the likelihood of initiation. Greater exposure to promotion leads to higher risk. This is seen in diverse cultures and persists when other risk factors, such as socioeconomic status or parental and peer smoking, are controlled. Causality is the only plausible scientific explanation for the observed data. The evidence satisfies the Hill criteria, indicating that exposure to tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
0
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(163 citation statements)
references
References 108 publications
7
143
0
11
Order By: Relevance
“…The exact timing, duration and magnitude of the smoking epidemic might vary significantly from one country to another and from male to female [44]. The tobacco industry recruits and retains smokers by associating its products with excitement, independence, sexuality and a "cool" style [33,45]. The symbolic value of smoking, representing adolescent freedom and independence, is reinforced through tobacco advertising [32,46,47]; the harm to children and adolescents has become apparent [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact timing, duration and magnitude of the smoking epidemic might vary significantly from one country to another and from male to female [44]. The tobacco industry recruits and retains smokers by associating its products with excitement, independence, sexuality and a "cool" style [33,45]. The symbolic value of smoking, representing adolescent freedom and independence, is reinforced through tobacco advertising [32,46,47]; the harm to children and adolescents has become apparent [45].…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco industry recruits and retains smokers by associating its products with excitement, independence, sexuality and a "cool" style [33,45]. The symbolic value of smoking, representing adolescent freedom and independence, is reinforced through tobacco advertising [32,46,47]; the harm to children and adolescents has become apparent [45]. A recent WHO report has revealed how commercial companies have successfully marketed cigarettes designed specifically for women [13,48] and direct advertising devoted to the female population [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unger et al (1997) who carried out a longitudinal study for two years on adolescents, found that adolescents who were in the "susceptible" category in the 7 th grade were 3 times more at risk to try smoking after a period of 2 years compared to those in the "nonsusceptible" category. Meanwhile, Difranza et al (2006) reported that susceptible adolescents were 2-3 times more likely to become experimental smokers. Also, Jackson, (1998) found that cognitive susceptibility was the main predictor contributing to smoking initiation among primary school students after a period of one year.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted around the world have found that youth with high exposure and awareness levels to protobacco messaging, whether through advertising, point-of-sale displays, depictions in movies, or promotional materials, are more likely to smoke. [8][9][10][11] In 2003, the World Health Assembly responded to the global tobacco epidemic by adopting the Framework Convention on Tobacco Control (FCTC). Article 13 of the FCTC addresses tobacco advertising, promotion, and sponsorship, whereas Article 11 focuses on tobacco packaging and labeling; however, there is evidence and concern that there is still a long way to go to achieve full implementation of the recommended provisions.…”
mentioning
confidence: 99%